A comparative study on asphalt binder and mixture performance of two traffic lanes during hot in-place recycling (HIR) procedure. (30th October 2019) - Bouraima, Mouhamed Bayane; Zhang, Xiao Hua; Rahman, Ali; Qiu, Yanjun
Highlights: Comparing two traffic lanes during hot in-place recycling procedure. Assessing physical and rheological properties of recycled asphalt binders. Conducting performance-based tests methods on mixtures. Discrepancy between properties of extracted materials of two traffic lanes. Difference in stress loading condition as a contributed factor for this variation. Abstract: With increasing number of roads shifting from the phase of construction to the phase of maintenance, using hot in-place recycling (HIR) has been a topical subject in China. The performance of asphalt materials has been investigated during HIR procedure in the past; however, no study has been conducted on properties of these materials from different traffic lanes. In this paper, the key properties of recycled asphalt binders and mixtures from two traffic lanes during HIR were analyzed and compared. The physical testing properties of asphalt binder, i.e. penetration, ductility, softening point and viscosity, and rheological testing properties including multi-stress creep recovery (MSCR) test and beam bending rheometer (BBR) test were carried out. Meanwhile, the performance-based test methods of recycled mixtures, i.e. wheel tracking test, three-point bending test, moisture susceptibility test and Marshall stability test were conducted. Results indicated that the extracted asphalt binders from slow lane had better rutting resistance while those of the emergency lane had superior low-temperature cracking resistance. Moreover, it was revealed that mixtures from the slow lane exhibited better rutting and moisture resistance, and mechanical performance while mixtures of emergency lane outperformed in terms of the low-temperature cracking resistance. Variation in materials properties of two traffic lanes were owing to the difference in stress loading condition of each lane.